2013
DOI: 10.5897/ijnm12.017
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of student nurses toward clinical work

Abstract: Clinical work in nursing education is an important component of the nursing curriculum aimed at actively engaging student nurses with the necessary skills needed for the nursing profession. The attitude of nursing students toward clinical work is becoming a topic of interest for nursing researchers. The objectives of the study were to determine the perspective of practicing nurses on students' attitude toward clinical work. Structured and semi-structured questionnaires were administered to determine the attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 22 publications
0
29
1
2
Order By: Relevance
“…In line with previous research, [10][11][12] this study also showed that nursing students had a positive attitude towards clinical experience and that clinical practice and available opportunities provided a reflection of the process of becoming a professional nurse. This is contrary to Awuah-Peasah et al 's [5] finding that nursing students had a negative attitude towards clinical exposure. This was Research apparently seen in their behaviour during clinical training, which included nursing students reporting late for work, being absent from clinical work without permission, using mobile phones during clinical working hours and lacking commitment to clinical work.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In line with previous research, [10][11][12] this study also showed that nursing students had a positive attitude towards clinical experience and that clinical practice and available opportunities provided a reflection of the process of becoming a professional nurse. This is contrary to Awuah-Peasah et al 's [5] finding that nursing students had a negative attitude towards clinical exposure. This was Research apparently seen in their behaviour during clinical training, which included nursing students reporting late for work, being absent from clinical work without permission, using mobile phones during clinical working hours and lacking commitment to clinical work.…”
Section: Discussioncontrasting
confidence: 89%
“…[4] Attitude plays a major role in guiding human behaviour towards achievement of goals, awareness of consequences and effective processing of complex information regarding the learning environment. [5] An important part of working with undergraduate nursing students is therefore building a positive attitude to clinical exposure as a vital component of their training. Attitude to clinical exposure can crucially influence nursing skills and competence once the student nurse graduates and cares for hospital patients.…”
mentioning
confidence: 99%
“…For instance, nursing students perceive empathy in regard to "being a good nurseˮ as nurses' ability to identify patients' feelings in an attempt to satisfy their needs within the nurse-patient/nurse-relatives relationship. This is linked to value of humanity, i.e., good nurses adhere to the principle that all patients must be treated equally, their dignity must be honoured, they must be accepted as they are, and treated with respect (Horton, Tschudin, Forget, 2007;Awuah-Peasah, Sarfo, Asamoah, 2013;Lachman, 2012). Nursing students underlined that 'being a good nurse' means demonstrating such features as sensitivity and kindness; however, to perform their duties in a competent manner, nurses must be able to manage their personal emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The first exposure of nurses to instruction either improves their learning autonomy or makes them more dependent on instructors out of fear [4]. This can have a major effect on the role of educated professional nurses [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to recommend a set of clinical teaching strategies that will be equally effective in every nursing education program. The faculty must decide which clinical teachings are congruent with the planned curriculum and relevant to its context [4].…”
Section: Introductionmentioning
confidence: 99%